Governing equation for a rocket going around the sun and returning to the earth - Wang, Yuchen (Transactions on Computer Science and Intelligent Systems Research, 2024)
In the article, the author mainly focuses on how to launch a rocket from the earth to go around the sun and return to the earth. The equation and solution of this motion are obtained by means of Newtonian mechanics, calculus and conic curve. To find the expression of the trajectory of the rocket, the article will obtain Kepler’s Law by using Newton’s Law, after setting a polar coordinate system. Similarly, plenty of mathematical methods are used to obtain the result in the article, hence, the combination of mathematic with physics and the application of pure mathematic is the tenet of the article. The most important mathematical method is solving differential equation, which is widely used in not only mechanics, but even quantum mechanics. After obtaining the solution, the author plugs the values into the analytic expression, in order to better reflect the actual role of the research results.